Functional TLR5 genetic variants affect human colorectal cancer survival - Klimosch, Sascha Niclas; Försti, Asta; Eckert, Jana; Knežević, Jelena; Bevier, Melanie; Schönfels, Witigo von; Heits, Nils; Walter, Jessica; Hinz, Sebastian; Lascorz, Jesus; Hampe, Jochen; Hartl, Dominik; et al. (Cancer research, 2013)
Toll-like receptors (TLR) are overexpressed on many types of cancer cells, including colorectal cancer cells, but little is known about the functional relevance of these immune regulatory molecules in malignant settings. Here, we report frequent single-nucleotide polymorphisms (SNP) in the flagellin receptor TLR5 and the TLR downstream effector molecules MyD88 and TIRAP that are associated with altered survival in a large cohort of Caucasian patients with colorectal cancer (n = 613). MYD88 rs4988453, a SNP that maps to a promoter region shared with the acetyl coenzyme-A acyl-transferase-1 (ACAA1), was associated with decreased survival of patients with colorectal cancer and altered transcriptional activity of the proximal genes. In the TLR5 gene, rs5744174/F616L was associated with increased survival, whereas rs2072493/N592S was associated with decreased survival. Both rs2072493/N592S and rs5744174/F616L modulated TLR5 signaling in response to flagellin or to different commensal and pathogenic intestinal bacteria. Notably, we observed a reduction in flagellin-induced p38 phosphorylation, CD62L shedding, and elevated expression of interleukin (IL)-6 and IL-1β mRNA in human primary immune cells from TLR5 616LL homozygote carriers, as compared with 616FF carriers. This finding suggested that the well-documented effect of cytokines like IL-6 on colorectal cancer progression might be mediated by TLR5 genotype-dependent flagellin sensing. Our results establish an important link between TLR signaling and human colorectal cancer with relevance for biomarker and therapy development. Cancer Res; 73(24); 7232-42. ©2013 AACR.
Gesehen am 19.03.2021